Special Aspects of Microstructure, Deformation and Fracture of Bioinert Zirconium and Titanium-Niobium Alloys in Different Structural States; Russian Physics Journal; Vol. 61, No. 9 - Sharkeev Yu. P. Yury Petrovich; Skripnyak V. A. Vladimir Albertovich; Vavilov V. P. Vladimir Platonovich; Legostaeva E. V. Elena Viktorovna; Kozulin A. A.; Chulkov A. O. Arseniy Olegovich; Eroshenko A. Yu. Anna Yurjevna; Belyavskaya O. A. Olga Andreevna; Skripnyak V. V. Vladimir Vladimirovich; Glukhov I. A. Ivan Aleksandrovich (2019, 2019)
Title screen